2018
DOI: 10.1186/s12936-018-2507-y
|View full text |Cite
|
Sign up to set email alerts
|

Baseline entomologic data on malaria transmission in prelude to an indoor residual spraying intervention in the regions of Alibori and Donga, Northern Benin, West Africa

Abstract: BackgroundDespite the success of indoor residual insecticide spraying (IRS) in Africa, particularly in Benin, some gaps of information need to be filled to optimize the effectiveness of this intervention in the perspective of the country’s effort to eliminate malaria. In anticipation to the 2018 IRS campaign in two targeted regions of northern Benin, this study aimed, to collect baseline information on vector composition, spatio-temporal variation and peak malaria transmission in the Alibori and Donga, two tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 47 publications
(37 reference statements)
7
28
3
Order By: Relevance
“…Such an observation was also made in Equatorial Guinea [32,[37][38][39][40]. However, recent data from Benin reported higher HBRs indoors than outdoors [36].…”
Section: Density and Human Blood Indexmentioning
confidence: 52%
See 2 more Smart Citations
“…Such an observation was also made in Equatorial Guinea [32,[37][38][39][40]. However, recent data from Benin reported higher HBRs indoors than outdoors [36].…”
Section: Density and Human Blood Indexmentioning
confidence: 52%
“…This could be due to the side effect of ongoing control measures like LLINs in these places as An. gambiae s.l., which were known to be more endophagic than exophagic [36]. Indeed, several studies have shown changing its biting and resting behavior from indoors to outdoors when LLINS were widely used in an area.…”
Section: Density and Human Blood Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Female mosquitoes seek blood meals late at night in human dwellings [6][7][8], where they are vulnerable. Although malaria is mostly transmitted indoors, some studies in East and West Africa have shown malaria transmission occurring outdoors by mosquitoes that escape insecticides or other indoor control methods [9][10][11][12]. Mosquito entry rate and consequent disease transmission are affected by house type [13], and it is widely acknowledged that poor quality housing -constructions with wooden roofs, straw, clay bricks and roof plates, or clay roofs, for example -is generally believed to be an important contributor to ill health [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mosquito entry rate and consequent disease transmission are affected by house type [13], and it is widely acknowledged that poor quality housing -constructions with wooden roofs, straw, clay bricks and roof plates, or clay roofs, for example -is generally believed to be an important contributor to ill health [14]. Recently, new approaches based on the design of house ceilings, doors, windows and eaves were developed to block and reduce mosquitoes entering into houses and thus transmitting disease [12][13][14]. Furthermore, approaches that exploit insect behaviour with regards to house entry have been explored as part of malaria vector control strategies [17,18].…”
Section: Introductionmentioning
confidence: 99%